Middlewest the complete tale - Young, Skottie 1978- (Image Comics, 2023)
"For most of his life, Abel has lived under a cloud of fear, worried he could unleash the monster raging just below the surface of his father, Dale. When a violent storm levels his sleepy Middlewest town, Abel and his childhood companion, Fox, must hastily flee from his father and the only home he's ever known, entering into a world of mystical carnies and soothsayer hobos, bridge trolls and wilderness spirits, endless forests and forgotten children. -- Back cover
Subtitle from cover
Previously published as a multi-volume set in 2019
"Contains material originally published in single magazine form as Middlewest #1-18"--Colophon
Includes "Middlewest: Extras" (exclusive bonus features)
Keywords: Foxes; Storms; Human-animal relationships; Vater; Junge -- 11-14 Jahre; Fantasiewelt; Flucht; Fuchs; Sturm; USA -- Mittlerer Westen; Fathers and sons / Comic books, strips, etc; Imaginary places / Comic books, strips, etc; Middle West / Comic books, strips, etc; Comics (Graphic works); Action and adventure comics; Comic; Fantasy comic books, strips, etc; Fantasy comics